في جودة الخدمات الصحية KAIZEN تبني نظام التحسين المستمر : دراسة تحليلية في مدينة طب الموصل - د. عادل محمد عبدالله (PROSPECTIVE RESEARCHES, 2023)
One of the factors which helps in providing high quality service is the integration between three elements, namely human resources, facility resource and consumer' satisfaction. Any flaw in any of these elements affects negatively the others. In this context, the problem of the research depends on two dimensions which are correlative and each of them explains the other. The first dimension involves the continuous progress in health services with the ability to climinize wasting. As for the second one, it is decreasing the quality of health services through different systems for the processes of service presenting. However, the question of the research is "How could one keep the improvement of health services progress?”. After many field visits and direct contact with the staff member of the organizations under research, the researcher hypothesizes that the change of the administration's way of thinking and minimizing of the loss of the resources as well as improving work prcedures may help in achieving a continuous improvement for high quality. This research aims at achieving values from continuous improving depending on KAIZEN system on systematic and continuous way and which minimizes waste. The research comes up with a conclusion that the improvement of health services quality whether financial or human resources have a vital role in the improvement of quality. It is also noticed that leaving departments inside the hospital or moving between hospitals leads to different type of waste.